Effectiveness of triple benefit health education intervention on knowledge, attitude and food security towards malnutrition among adolescent girls in Borno State, Nigeria - Shapu, Ruth Charles; Ismail, Suriani; Lim, Poh Ying; Ahmad, Norliza; Garba, Hussaini; Njodi, Ibrahim Abubakar (MDPI, 2022)
Knowledge and attitude are essential components of food security as malnutrition remains a critical public health concern among adolescents. The study evaluates the effectiveness of a Triple Benefit Health Education Intervention on knowledge, attitude and food security towards malnutrition among adolescent girls. This was a cluster randomized controlled trial among 417 randomly selected adolescent girls aged 10 to 19 years old in Maiduguri, Borno state, Nigeria from October 2019 to March 2020. About 208 respondents were assigned to experimental while 209 to control group, respectively, using an opaque sealed envelope. A structured questionnaire using KoBo Collect Toolbox was used for the collection of data at baseline, three and six-months post intervention while the data collected were analyzed using generalized estimating equation (GEE). The outcome of the baseline shows no statistically significant difference in sociodemographic characteristics, knowledge, attitude and food security between experimental and control groups. The study reveals a statistically significant difference between experimental and control groups for knowledge (p < 0.001; p < 0.001), attitude (p < 0.001; p < 0.001) and food security (p = 0.026; p = 0.001) at three and six-months post intervention, respectively. The triple benefit health education intervention package employed in this study can serve as an intervention tool to combat malnutrition among adolescent girls in Nigeria at large.